Optical encryption method using toroidal zone plates (2005)
ABSTRACT: We present the implementation of an optical encryption method using zone plates. The optical security system is based on a computer generated phase mask. In particular, for this proposal the selected phase mask is a toroidal zone plate. In the encryption process we use an optical processor where this phase mask is placed in the Fourier plane of the object to be encrypted. The original-data recovering is performed by digital reconstruction using the conjugate of the encryption mask. The different phase encoding procedures show that the diffraction efficiency of zone plates is relevant to the decryption process. Computer simulations are presented to demonstrate the validity of the method.